Effect of edge geometry on PVD-TiN coated carbide tools when face milling titanium alloy, Ti-6246 - Sharif, Safian (2007)
This paper presents the experimental investigation on the effect of edge geometry of coated carbide inserts on cutting performance during face milling of titanium alloy, Ti-6Al4V. Two similar PVD-TiN coated inserts with different edge geometry were used in the face milling experiment at various cutting speeds of 55, 65 80 and 100 m/min with a feed rate of 0.1mm/tooth. Tool life and tool failure characteristics were examined at the above cutting conditions. Results showed that edge geometry had a significant effect on the tool performance. Insert with sharp cutting edge was observed to perform better than chamfered edge insert at all conditions investigated. Excessive chipping at the cutting edge and chipping and/or flaking on the rake face were the dominant failure modes on both tools under most cutting conditions.